2015
DOI: 10.1590/s0102-67202015000300010
|View full text |Cite
|
Sign up to set email alerts
|

Copaiba Oil Influences Ventral Hernia Repair With Vicryl® Mesh?

Abstract: Background: The use of meshes in hernia surgical repair promoted revolution in the surgical area; however, some difficulties had come, such as a large area of fibrosis, greater postoperative pain and risk of infection. The search for new substances that minimize these effects should be encouraged. Medicinal plants stand out due possible active ingredients that can act on these problems. Aim: To check the copaiba oil influence in the repair of abdominal defects in rats corrected with Vicryl(c) mesh. Method: Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…Thus, we have looked at some works with copaiba oil administered via gavage for abdominal adhesion in rats corrected with Vicryl (Ethicon Inc., Somerville, NJ, USA) mesh. 26 The authors demonstrated that although the gavage administration showed no statistically significant difference in adhesions and collagen fibers, the inflammatory response was better in the group that used copaiba oil. Copaiba oil also showed positive effects on bladder healing, 11 and skin healing processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we have looked at some works with copaiba oil administered via gavage for abdominal adhesion in rats corrected with Vicryl (Ethicon Inc., Somerville, NJ, USA) mesh. 26 The authors demonstrated that although the gavage administration showed no statistically significant difference in adhesions and collagen fibers, the inflammatory response was better in the group that used copaiba oil. Copaiba oil also showed positive effects on bladder healing, 11 and skin healing processes.…”
Section: Resultsmentioning
confidence: 99%
“…However, we cannot fail to report that the studies found on the healing properties of copaiba did not involve its application oil on the skin exclusively. Yasoshima et al 26 used copaiba oil via gavage in rats that underwent hernia repair with Vicryl mesh. According to the authors, there were no significant results in the postoperative healing process when compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…It can be divided into three phases: 1 st or exudative inflammation; 2 nd or proliferative/ fibroblastic (granulation tissue with deposition of extracellular matrix); 3 rd or remodeling/maturation [1][2][3][4][5][6] . The knowledge of each of these stages is important to guide appropriate adjuvant therapy to improve biological reaction 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Several substances have been studied both clinically and experimentally, such as ethanolamine oleate, diazepam, erythromycin, macrolides, quinolones, povidone-iodine, in search of an agent with the following characteristics: effective, widely available, low cost, and few side effects 6 . Currently, the most commonly used agents are talc instilled into the pleural cavity by aspersion or dilution in saline solution, tetracycline derivatives (minocycline and doxycycline), and bleomycin [7][8][9][10] . In the 1980s, tetracycline was the preferred agent for chemical pleurodesis.…”
Section: Introductionmentioning
confidence: 99%